Medical crowdfunding in a healthcare system with universal coverage: an exploratory study - Ágnes Lublóy (BMC, 2020)
Abstract Background In recent years, crowdfunding for medical expenses has gained popularity, especially in countries without universal health coverage. Nevertheless, universal coverage does not imply covering all medical costs for everyone. In countries with universal coverage unmet health care needs typically emerge due to financial reasons: the inability to pay the patient co-payments, and additional and experimental therapies not financed by the health insurance fund. This study aims at mapping unmet health care needs manifested in medical crowdfunding campaigns in a country with universal health coverage. Methods In this exploratory study we assess unmet health care needs in Germany by investigating 380 medical crowdfunding campaigns launched on Leetchi.com . We combine manual data extraction with text mining tools to identify the most common conditions, diseases and disorders which prompted individuals to launch medical crowdfunding campaigns in Germany. We also assess the type and size of health-related expenses that individuals aim to finance from donations. Results We find that several conditions frequently listed in crowdfunding campaigns overlap with the most disabling conditions: cancer, mental disorders, musculoskeletal disorders, and neurological disorders. Nevertheless, there is no strong association between the disease burden and the condition which prompted individuals to ask for donations. Although oral health, lipoedema, and genetic disorders and rare diseases are not listed among leading causes of disability worldwide, these conditions frequently prompted individuals to turn to crowdfunding. Unmet needs are the highest for various therapies not financed by the health insurance fund; additional, complementary, and animal-assisted therapies are high on the wish list. Numerous people sought funds to cover the cost of scientifically poorly supported or unsupported therapies. In line with the social drift hypothesis, disability and bad health status being associated with poor socioeconomic status, affected individuals frequently collected donations for their living expenses. Conclusions In universal healthcare systems, medical crowdfunding is a viable option to finance alternative, complementary, experimental and scientifically poorly supported therapies not financed by the health insurance fund. Further analysis of the most common diseases and disorders listed in crowdfunding campaigns might provide guidance for national health insurance funds in extending their list of funded medical interventions. The fact of numerous individuals launching crowdfunding campaigns with the same diseases and disorders signals high unmet needs for available but not yet financed treatment. One prominent example of such treatment is liposuction for patients suffering from lipoedema; these treatments were frequently listed in crowdfunding campaigns and might soon be available for patients at the expense of statutory health insurance in Germany.